Study on Food Safety by Detection of Contamination in Food of the Market at LuangPrabang - CHANTHAKHOUN, Vongpasith; MANYSOAT, Soutthanou; BRIATIA, Xoxong; BANDAVONG, Viraxay (Souphanouvong University Journal Multidisciplinary Research and Development, 2017)
The study of Food Safety by Detection of Contamination on Food at the Market in Luang Prabang Province. The study was to analyses the contamination by formalin, pesticide residues, E. coli, salmonella spp. in different types of food (e.g., vegetable, animal products, aquatic products, and NTFPs) at retail markets in LuangPrabang district (3 Markets as LuangPrabang, Nam Bak and Phonxay msrkets). A total of 494 samples were collected and were analyzed using standard protocols. Results revealed that samples of pesticide residues from LuangPrabang, Nam Bak and Phonxay markets were 47.14, 35.18 and 59.18% respectively; formalin were 6.00, 12.77 and 10.00% respectively; E. coli (6.00 and 4.26% respectively) and Salmonella (34.00 and 17.02% respectively) were found at LuangPrabang, and Nam Bak. However, all the sample E. coli and Salmonella not contaminated at Phonxay markets. Therefore, the results indicate that food list were thinks before brought because of chemical and bacterial contamination in food from 3 Markets particularly, pesticide residues (White Radish, Salad, Big Chili, Tomato, small orange, Apple, Dragon fruits and Melon); formalin (Fresh squid, dry Squid, Smoked fish, Chicken freeze, Reticulum); E.coli and Salmonella in animal products (pork, beef, reticulum, Fresh Squid and dry Squid). Therefore results indicate that food quality and hygiene controls should be made more stringent and should include restaurants, guesthouse and hotels. Meanwhile, authorities should work proactively to advise the farmers and retails in the markets to understand the risk of contamination and regulation from the governor. However, further research is required to elucidate to promotion by training to the governor staff and markets authorizes as the key to food quality and hygiene controls.